Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 447881 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Accipiter striatus" ] } The dataset includes 447881 records from 149 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0003301-150422101436696/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences